Optical fiber article, and production and use thereof
By coating the functional layers of sensory silane and alkyl silane on the surface of the fiber, the problems of high corrosion, short life, easy folding and poor biocompatibility in medical equipment are solved, and higher corrosion resistance, life and safety are achieved.
Patent Information
- Application Number
- JP2024189858
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-08-17
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing optical fibers have problems in medical equipment such as high corrosion, short life, easy folding, poor biocompatibility and possible harmful photopolymers. Especially when used in high pressure, high temperature and high humidity environments, which affect the reliability and safety of the equipment.
Optical fibers containing functional layers are used, which are composed of sensory silanes and/or alkyl silanes. They are combined with the fiber surface through covalent bonds or hydrogen bonds to improve the adhesion and mechanical stability of the fiber, reduce microcracks and folds, and avoid the use of harmful photopolymers.
It improves the corrosion resistance, life and biocompatibility of optical fibers, reduces the content of harmful substances, and ensures stability and safety in high pressure, high temperature and high humidity environments.
Smart Images

Figure 2025016612000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to fiber optic articles and methods for making the same. The present invention also relates to the use of the fiber optic articles in fiber bundles as light guides and / or image guides, for example in endoscopes.
[0002] Fiber optic articles, such as glass fiber articles, can transmit data and / or light as light guides and / or image guides. Fiber optic articles are frequently used in the medical field, for example for therapeutic and / or diagnostic methods. Light guides and / or image guides are used, for example, for flexible transmission of light in measuring instruments, microscopes, spectroscopes, inspection cameras and endoscopes. Medical instruments, such as endoscopes, are very often autoclaved and / or sterilized. In steam sterilization, these instruments are exposed to high pressure, high temperature and at the same time high humidity. Thus, light guides and / or image guides for use in medical instruments, such as endoscopes, need to have good autoclavability or sterilizability and high corrosion resistance in order to remain usable for a long time. Thus, there is a need for fiber optic articles that improve the longevity of medical instruments and reduce the occurrence of corrosion. Furthermore, fiber optic articles with high temperature resistance and moisture resistance would be desirable. At the same time, fiber optic articles should have high bending properties and good mechanical stability, especially for use in endoscopes.
[0003] In many cases, optical fibers are covered with a bundling agent as a protective layer. Usually, optical fibers are provided with a polymerizable coating composition that is cured by UV radiation. Such coating compositions often contain acrylates, methacrylates and other polymerizable components. However, such polymerizable coating compositions are of health concern. Furthermore, such coatings contain photoinitiators, the effects of which on human health are increasingly being questioned. In particular, the use of such photopolymerizable materials in medical devices that come into contact with human organs is problematic. Therefore, optical fiber articles that can be produced without health-hazardous components would be desirable. In particular, these materials should be as little or even completely toxic as possible and should not pose a risk to the patient. Therefore, it would be desirable to provide optical fibers with improved biocompatibility and reduced toxicity.
[0004] US 2003 / 0045600 describes sizing agents that may include silanes, such as polyalkoxysilanes and polyhalosilanes. The sizing agents of US 2003 / 0045600 may also include halides, such as chlorine or fluorine. Additionally, US 2003 / 0045600 describes sizing agents that may include polyether urethane acrylate as the main component.
[0005] WO 01 / 49625 describes optical fibers having a UV-curable sizing agent which may contain a photopolymerizable compound such as, for example, caprolactone (meth)acrylate or 4-hydroxybutyl (meth)acrylate. Furthermore, the sizing agent of WO 01 / 49625 may contain a photoinitiator such as, for example, 1-hydroxycyclohexyl phenyl ketone or 2,2-dimethoxy-2-phenylacetophenone.
[0006] It is therefore an object of the present invention to overcome the drawbacks of the prior art, in particular to provide an improved optical fiber article for use in medical and diagnostic equipment, such as endoscopes, which should be distinguished in particular by high corrosion resistance, even in steam sterilization, by a long service life, by good bending strength, as well as by particularly high biocompatibility and reduced toxicity.
[0007] These problems are solved by the subject matter of the claims. These problems are solved in particular by an optical fiber article comprising at least one optical fiber and a functional layer arranged on its surface. The optical fiber may have a fiber core and a cladding arranged on the fiber core.
[0008] The functional layer has the following structural formula: [ka]
[0009] [In the formula, Z is a branched or unbranched alkyl group or an aryl group having 1 to 18 carbon atoms, R1, R2 and R3 are independently selected from hydrogen, oxygen, alkyl, hydroxyalkyl and hydroxyl, and one, two or three of the groups R1, R2 or R3 are directly or indirectly attached to the surface via a covalent bond; and R4 is selected from -NH2, -NHR', -NR'R'', glycidyloxy and -SH, where R' and R'' are alkyl, aminoalkyl, hydroxyalkyl and -(CH2) m NH2, and m is 1 to 6. The compound may include at least one functional silane having the formula:
[0010] In one embodiment, the present invention provides an optical fiber article comprising at least one optical fiber and a functional layer disposed on a surface of the optical fiber, the functional layer having the following absorption in the IR spectrum: a. 1500cm -1 ~1900cm -1 Maximum absorption band height in the range of 800 cm -1 ~1200cm -1 the ratio of maximum absorption band heights in the range of at least 2.0; b. 1500cm -1 ~1900cm -1 Maximum absorption band height in the range of 2700 cm -1 ~3000cm -1 the ratio of maximum absorption band heights in the range of at least 2.0; and c. 2700cm -1 ~3000cm -1 Maximum absorption band height in the range of 800 cm -1 ~1200cm -1 The ratio of the maximum absorption band heights in the range of at least 1.1 and at most 2.0 The present invention relates to an optical fiber article characterized in that
[0011] An optical fiber article having such an IR spectrum is obtained when the procedures described herein are carried out. In a particularly preferred embodiment, the functional layer has an IR spectrum substantially according to FIG.
[0012] "Optical fiber" refers to a fiber capable of transmitting light over short or long distances. Such an optical fiber can be, for example, a glass fiber. An optical fiber includes a core layer (also called "fiber core"), a cladding layer (also called "cladding" for short), and a functional layer disposed on the surface of the cladding layer.
[0013] A "fiber optic bundle" refers to a plurality of optical fibers. For example, a fiber optic bundle may consist of 10 or more optical fibers.
[0014] "Fiber optic article" refers to an article that includes at least one optical fiber. Fiber optic articles may also include multiple optical fibers. Optical fibers and fiber optic articles may be used, for example, in light guides and / or image guides. For use in such light guides and / or image guides, for example, multiple fiber optic articles may be bonded together and embedded together within a sleeve.
[0015] "Functional layer" refers to a layer arranged on the surface of the cladding layer that at least partially, in particular substantially completely, covers the optical fiber. The functional layer serves in particular to protect the optical fiber, for example against breakage. The functional layer can be formed, for example, from a bundling agent.
[0016] "Bundling agent" refers to a composition that serves to apply a functional layer onto an optical fiber. The bundling agent can be applied after the fiber is manufactured, for example, by dipping, spraying, or roll-to-roll processes.
[0017] "Functional silane" refers to a silane compound that includes at least one functional group capable of undergoing a chemical reaction. Such a functional group can be, for example, an amino group. Functional silanes can act, for example, as adhesion promoters and act as bridges between the surface of the cladding layer and the adhesive.
[0018] "Cladding layer" refers to a layer that is disposed under a functional layer and surrounds a core layer. The cladding layer may comprise, for example, glass or a polymer, such as polyimide. The cladding layer specifically contributes to the light transmitting function of the optical fiber.
[0019] "Core layer" refers to the inner layer of an optical fiber, which is surrounded by the cladding layer. The core layer may comprise, for example, glass or a polymer, such as polycarbonate. The core layer, together with the cladding layer, specifically contributes to the light transmitting function of the optical fiber.
[0020] In the following detailed description, measures and features that may contribute to the success of the present invention are listed, where it is not necessary to implement all measures in one optical fiber article, rather the intended improvement is already achievable if only some of the following measures are applied.
[0021] In one embodiment, the functional layer comprises a functional silane. The functional silane comprises a free functional group, such as an amino group, that is not reacted in the reaction with an acrylate or other reactive compound. The functional silane promotes good adhesion of the functional layer to the surface of the cladding layer. Good adhesion of the functional layer to the optical fiber serves the protective function of the functional layer, for example protection against microcracks and breakage, especially when the bending load of the fiber article is repeated and increased. Furthermore, the functional silane provides a good adhesion-promoting function to the functional layer on the side opposite the optical fiber. This allows the functional layer to adhere well to further materials, such as adhesives. With the functional silane, good adhesion of the optical fiber article is achieved. For example, when several optical fiber articles are embedded and bonded in a sleeve, the optical fiber articles achieve better adhesion to each other and to the sleeve. Such a sleeve may comprise, for example, stainless steel or plastic.
[0022] Preferably, the alkyl group of Z has at least 1 carbon atom, at least 2 carbon atoms, at least 3 carbon atoms or at least 4 carbon atoms. Preferably, the alkyl group of Z has at most 25 carbon atoms, more preferably at most 20 carbon atoms, more preferably at most 15 carbon atoms, more preferably at least at most 12 carbon atoms, more preferably at most 10 carbon atoms, more preferably at most 9 carbon atoms, more preferably at most 8 carbon atoms, more preferably at most 7 carbon atoms. In an embodiment, the alkyl group of Z has 1 to 25 carbon atoms, more preferably at most 1 to 20 carbon atoms, more preferably at most 2 to 15 carbon atoms or at most 3 to 12 carbon atoms. In a particularly preferred embodiment, the alkyl group of Z has 3 to 8 carbon atoms. The number of carbon atoms affects the gliding properties of the optical fiber, which allows the optical fiber or optical fiber article to be bent more frequently and more strongly without breaking. Similarly, the improved gliding properties allow the optical fibers to slide well past each other and at the same time not to adhere to each other. Preferably, the alkyl group of Z is an unbranched alkyl group.
[0023] The groups R1, R2 and R3 may be selected independently from hydrogen, oxygen, alkyl, alkyloxy, hydroxyalkyl and hydroxyl, with one, two or three of the groups R1, R2 or R3 being directly or indirectly bonded to the surface of the optical fiber via a covalent bond. That is, for example, one of the groups R1, R2 or R3 may be an alkyl group (e.g., a methyl group) or an alkyloxy group (e.g., a methoxy or ethoxy group), with the two further groups being oxygen and being bonded to the surface of the fiber via a siloxane group (see FIG. 1). The alkyl component of R1, R2 and / or R3 may have a chain length of 1 to 6 carbon atoms, in particular 1 to 3 carbon atoms. In particular, one, two or three of the groups R1, R2 or R3 of the functional silane are directly or indirectly bonded to the surface of the fiber via a covalent bond. Preferably, one, two or three of the groups R1, R2 and R3 are (-XR''') groups, where X is selected from oxygen, selenium and sulfur, and R''' is selected from an alkyl group, hydrogen and the surface of the fiber. More preferably, one, two or three of the groups R1, R2 and R3 are (-XR''') groups, where X is oxygen and R''' is selected from an alkyl group, hydrogen and the surface of the fiber. More preferably, one, two or three of the groups R1, R2 and R3 are (-XR''') groups, where X is oxygen and R''' is the surface of the fiber. More preferably, two or three of the groups R1, R2 and R3 are (-XR''') groups, where X is oxygen and R''' is the surface of the fiber. The alkyl group may have a carbon chain length in the range of 1 to 6 carbon atoms, in particular 1 to 3 carbon atoms. For example, the functional silanes form one, two or three siloxane bonds with the surface of the cladding layer, thereby making the functional silanes described herein a significant contributor to the attachment of the functional layer to the optical fiber.
[0024] R4 may be selected from -NH2, -NHR', -NR'R'', glycidyloxy and -SH, where R' and R'' are alkyl, aminoalkyl, hydroxyalkyl and -(CH2) mand m is 1 to 6, in particular 1 to 3. In a preferred embodiment, R4 is selected from -NH2, -NHR', -NR'R'', where R' and R'' are alkyl, aminoalkyl, hydroxyalkyl and -(CH2) m Preferably, R4 is selected from -NH2 and -NH2, and m is 1 to 6, more preferably m is 1 to 5, more preferably 1 to 4, more preferably 1 to 3, and even more preferably 1 to 2. Particularly preferably, R4 is selected from -NH2 and -NHR', where R' is alkyl, aminoalkyl, hydroxyalkyl, and -(CH2) m Preferably, R4 is selected from -NH2, m is 1 to 6, more preferably m is 1 to 5, more preferably 1 to 4, more preferably 1 to 3, more preferably 1 to 2. Particularly preferably, R4 is selected from -NH2 and -NHR', where R' is alkyl. In a particularly preferred embodiment, R4 is -NH2. In a particularly preferred embodiment, R4 is -(CH2)2NH2. Functional silanes with such groups R4 allow good adhesion promotion and bonding, for example when optical fiber articles are embedded in sleeves with adhesives.
[0025] In a particularly preferred embodiment, the functional silane has the following structural formula: [ka]
[0026] [wherein R1, R2 and R3 are (-XR''') groups, where X is oxygen and R''' is the surface of the fiber, where Z is an unbranched alkyl group having 3 carbon atoms, and where R4 is selected from -NH2 and -NHR', where R'' is -(CH2) m NH2, m=2] has.
[0027] In a particularly preferred embodiment, the functional silane has the following structural formula: [ka]
[0028] wherein R1, R2 and R3 are (-XR''') groups, where X is oxygen and R''' is the surface of the fiber, where R4 is -NH2, and where Z is an unbranched alkyl group having 1 to 10 carbon atoms, more preferably 2 to 9 carbon atoms, and more preferably 3 to 8 carbon atoms. has.
[0029] In another particularly preferred embodiment, the functional silane has the following structural formula: [ka]
[0030] [wherein R1, R2 and R3 are (-XR''') groups, where X is oxygen and R''' is the surface of the fiber, where R1, R2 and R3 are directly attached to the surface of the fiber via covalent bonds, and where R4 is -NHR', where R' is -(CH2) m NH2, m=2, and wherein Z is an unbranched alkyl group having 1-10 carbon atoms, more preferably 2-9 carbon atoms, and even more preferably 3-8 carbon atoms. has.
[0031] In a preferred embodiment, Z=3, R4 is NH2 or NHR', and R'=-(CH2) mNH2 and m=2. Examples of functional silanes preferably used according to the invention are N-[3-(trimethoxysilyl)propyl]ethylenediamine, N-[3-(triethoxysilyl)propyl]ethylenediamine, 3-aminopropyl-diethoxy-methylsilane, 3-glycidyloxypropyl-triethoxysilane, 3-glycidoxypropyldimethoxymethylsilane, 3-glycidoxypropyldiethoxymethylsilane and combinations thereof or their reaction products with the surface of the fiber, in particular their derivatives bound to the surface of the fiber via one, two or three covalent bonds.
[0032] In certain embodiments, the functional layer comprises a plurality of functional silanes, hi certain embodiments, the functional layer comprises at least two functional silanes, at least three functional silanes, or at least four functional silanes.
[0033] Preferably, the functional layer comprises at least 0.1% by weight, more preferably at least 0.5% by weight, more preferably at least 0.9% by weight, more preferably at least 1.2% by weight, more preferably at least 1.5% by weight, more preferably at least 1.8% by weight, more preferably at least 2% by weight. Preferably, the functional layer comprises at most 70% by weight, more preferably at most 60% by weight, more preferably at most 50% by weight, more preferably at most 40% by weight, more preferably at most 30% by weight, more preferably at most 25% by weight, more preferably at most 15% by weight. In a preferred embodiment, the functional layer comprises at most 0.1-70% by weight, more preferably at most 0.5-50% by weight, more preferably at most 0.9-40% by weight, more preferably at most 1.2-30% by weight, more preferably at most 1.5-15% by weight. In a particularly preferred embodiment, the functional layer comprises at most 1-40% by weight or at most 2-15% by weight of functional silane. If the proportion of functional silane is too low, the functional layer will not adhere well to the surface of the cladding layer, so that the optical fiber will be prone to microcracks and breakage. If the proportion of functional silane is too high, the optical fibers will not slide well against each other and will tend to stick to each other. This will increase the formation of microcracks and breakages when bending loads are repeated and increased. It should be noted that the sizing agent used to manufacture the functional layer is preferably substantially free of polymerizable solvents such as acrylates or methacrylates, so that the content of functional silane in the functional layer is relatively high compared to that of the prior art functional layer. The solvent used in the sizing agent will not remain in the functional layer after drying.
[0034] In an embodiment, the functional layer comprises at least one alkylsilane instead of or in addition to the functional silane. Preferably, the functional layer comprises an alkylsilane covalently bonded to the surface of the fiber. Preferably, the alkylsilane has the following structural formula: [ka]
[0035] wherein R5, R6 and R7 are independently selected from hydrogen, oxygen, alkyl, alkyloxy, hydroxyalkyl and hydroxyl, and one, two or three of the groups R5, R6 or R7 are directly or indirectly attached to the surface of the fiber via a covalent bond; R8 is selected from branched and unbranched alkyl groups having 1 to 25 carbon atoms. The alkylsilane improves the hydrolysis resistance and reduces the surface energy of the optical fiber.
[0036] Preferably, the alkyl group R8 of the alkylsilane has at least 1 carbon atom, at least 2 carbon atoms, at least 5 or at least 8 carbon atoms. Preferably, the alkyl group R8 has up to 25 carbon atoms, more preferably up to 20 carbon atoms, more preferably up to 15 carbon atoms, more preferably at least up to 12 carbon atoms, more preferably up to 10 carbon atoms. In an embodiment, the alkyl group R8 has 1-25 carbon atoms, more preferably 1-20 carbon atoms, more preferably 1-15 carbon atoms, more preferably 3-12 carbon atoms. In a particularly preferred embodiment, the alkyl group R8 has 5-10 carbon atoms or 8-15 carbon atoms. The chain length of the alkylsilane according to the present invention improves the sliding of the optical fibers within the optical fiber bundle, for example, and prevents the optical fibers from adhering to each other. This improves the handling and re-separation of the optical fibers in the optical fiber bundle. Preferably, the alkyl group R8 of the alkylsilane is an unbranched alkyl group. Preferably, one, two or three of the groups R5, R6 and R7 are (-XR''') groups, where X is selected from oxygen, selenium and sulfur, and R''' is selected from an alkyl group, hydrogen and the surface of the fiber. More preferably, one, two or three of the groups R5, R6 and R7 are (-XR''') groups, where X is oxygen and R''' is selected from an alkyl group, hydrogen and the surface of the fiber. More preferably, one, two or three of the groups R5, R6 and R7 are (-XR''') groups, where X is oxygen and R''' is the surface of the fiber. More preferably, two or three of the groups R5, R6 and R7 are (-XR''') groups, where X is oxygen and R''' is the surface of the fiber. For example, the alkylsilane forms one or two or three siloxane bonds with the Si-OH groups on the surface of the fiber. The alkylsilanes described herein improve the adhesion of the functional layer to the surface of the fiber. Additionally, the alkylsilanes described herein improve the smoothness of the optical fibers, for example in optical fiber bundles, and reduce friction between the optical fibers.
[0037] Preferably, the alkylsilane has the following structural formula: [ka]
[0038] wherein R5, R6 and R7 are (-XR''') groups, where X is oxygen and R''' is the surface of the fiber, where R5, R6 and R7 are directly attached to the surface of the fiber via covalent bonds, and where R8 is an unbranched alkyl group having 1 to 15 carbon atoms, more preferably 1 to 12 carbon atoms, more preferably 1 to 10 carbon atoms, more preferably 1 to 9 carbon atoms, and more preferably 3 to 8 or exactly 8 carbon atoms. has.
[0039] Examples of alkylsilanes to be used according to the invention are trimethoxypropylsilane, trimethoxyoctylsilane, trimethoxymethylsilane, triethoxyoctylsilane, trimethoxydecylsilane, triethoxydecylsilane, trimethoxydodecylsilane, triethoxydodecylsilane, n-propyltriethoxysilane, triethoxymethylsilane, dimethoxydimethylsilane, diethoxydimethylsilane, or their reaction products with the surface of the fiber, in particular their derivatives bound to the surface of the fiber via one, two or three covalent bonds.
[0040] In certain embodiments, the functional layer comprises multiple alkylsilanes, hi certain embodiments, the functional layer comprises at least two alkylsilanes, at least three alkylsilanes, or at least four alkylsilanes.
[0041] Preferably, the functional layer comprises at least 0.8% by weight of alkylsilane, more preferably at least 1% by weight, more preferably at least 2% by weight, more preferably at least 3% by weight, more preferably at least 4% by weight, more preferably at least 5% by weight, more preferably at least 6% by weight. Preferably, the functional layer comprises at least one alkylsilane in a proportion of up to 65% by weight, more preferably up to 60% by weight, more preferably up to 55% by weight, more preferably up to 50% by weight, more preferably up to 45% by weight, more preferably up to 40% by weight, more preferably up to 35% by weight. In a preferred embodiment, the functional layer comprises 0.8-65% by weight, more preferably 1-60% by weight, more preferably 29-55% by weight, more preferably 3-50% by weight, more preferably 4-45% by weight. In a particularly preferred embodiment, the functional layer comprises 6-35% by weight of alkylsilane. If the proportion of alkylsilane is too low, the optical fiber will exhibit reduced smoothness and reduced chemical resistance, e.g., increased friction between optical fibers in an optical fiber bundle, which will lead to faster formation of microcracks and breaks. Furthermore, if the proportion of alkylsilane is too low, the optical fiber will exhibit reduced chemical stability, e.g., against acids. If the proportion of alkylsilane is too high, the optical fiber will exhibit reduced cohesion, e.g., between optical fibers in an optical fiber bundle.
[0042] In an embodiment, the functional layer comprises a polyethylene glycol (PEG) silane instead of or in addition to the functional silane and / or alkyl silane. Preferably, the functional layer comprises a PEG silane covalently bonded to the surface of the fiber. Preferably, the PEG silane has the following structural formula: [ka]
[0043] wherein R9, R10 and R11 are independently selected from hydrogen, oxygen, alkyl, alkyloxy, hydroxyalkyl and hydroxyl, and one, two or three of the groups R9, R10 and R11 are directly or indirectly bonded to the surface of the fiber via a covalent bond; and R12 has, consists of, or is a derivative of a polyethylene glycol group having a chain length of 5 to 900 ethylene oxide units. The PEG silane improves the hydrolytic stability of the optical fiber.
[0044] Preferably, the polyethylene glycol group or derivative thereof of R12 has a chain length of at least 3, more preferably at least 4, more preferably at least 5, more preferably at least 6, more preferably at least 7, and more preferably at least 8 ethylene oxide units. Preferably, the polyethylene glycol group or derivative thereof has a chain length of at most 30, more preferably at most 25, more preferably at most 20, more preferably at most 15, and more preferably at most 12 ethylene oxide units. In an embodiment, the polyethylene glycol group has a chain length of 3 to 30, more preferably 4 to 25, and more preferably 5 to 20 ethylene oxide units. In a particularly preferred embodiment, the polyethylene glycol group has a chain length of 8 to 12 ethylene oxide units. The chain length of the polyethylene glycol group or derivative thereof according to the present invention improves the cohesion of optical fibers, for example in an optical fiber bundle, without them being bonded to each other. Thereby, for example, the smoothness of the optical fibers in an optical fiber bundle is improved. The polyethylene glycol group of R12 may have an end group at its free end. The terminal groups may be hydroxyl or alkyloxy groups, especially methoxy groups.
[0045] Preferably, one, two or three of the groups R9, R10 and R11 are (-XR''') groups, where X is selected from oxygen, selenium and sulfur, and R''' is selected from an alkyl group, hydrogen and the surface of the fiber. More preferably, one, two or three of the groups R9, R10 and R11 are (-XR''') groups, where X is oxygen and R''' is selected from an alkyl group, hydrogen and the surface of the fiber. More preferably, one, two or three of the groups R9, R10 and R11 are (-XR''') groups, where X is oxygen and R''' is the surface of the fiber. More preferably, two or three of the groups R9, R10 and R11 are (-XR''') groups, where X is oxygen and R''' is the surface of the fiber. For example, the PEG silane forms one or two or three siloxane bonds with silicon groups on the surface of the fiber. The PEG silanes described herein improve the adhesion of the functional layer to the surface of the fiber. Additionally, the PEG silanes described herein improve the smoothness of the optical fibers, for example in fiber optic bundles, and reduce friction of the optical fibers against each other.
[0046] In a particularly preferred embodiment, the PEG silane has the following structural formula: [ka]
[0047] wherein R9, R10 and R11 are (-XR''') groups, where X is oxygen and R''' is the surface of the fiber, wherein R9, R10 and R11 are directly bonded to the surface of the fiber via covalent bonds, and wherein R12 has, consists of or is a derivative of a polyethylene glycol group having a chain length of 3 to 30 ethylene oxide units, more preferably 4 to 25 ethylene oxide units, more preferably 5 to 20 ethylene oxide units, and even more preferably 8 to 12 ethylene oxide units. has.
[0048] An example of a PEG silane that can be used according to the present invention is 2-[methoxy(polyethyleneoxy)] 9-12 propyl]trimethoxysilane, 2-[methoxy(polyethyleneoxy) 9-12 Propyl]triethoxysilane, 2-[ethoxy(polyethyleneoxy) 9-12 [propyl]triethoxysilane, [hydroxy(polyethyleneoxy)propyl]triethoxysilane, and their reaction products with the surface of the fiber, in particular their derivatives bonded to the surface of the fiber via one, two or three covalent bonds.
[0049] In certain embodiments, the functional layer comprises multiple types of PEG silanes, hi certain embodiments, the functional layer comprises at least two types of PEG silanes, at least three types of PEG silanes, or at least four types of PEG silanes.
[0050] Preferably, the functional layer comprises at least one PEG silane in a proportion of at least 1% by weight, more preferably at least 5% by weight, more preferably at least 8% by weight, more preferably at least 11% by weight, more preferably at least 13% by weight, more preferably at least 15% by weight, more preferably at least 21% by weight. Preferably, the functional layer comprises at least one PEG silane in a proportion of at most 90% by weight, more preferably at most 85% by weight, more preferably at most 80% by weight, more preferably at most 75% by weight, more preferably at most 70% by weight, more preferably at most 65% by weight, more preferably at most 62% by weight. In a preferred embodiment, the functional layer comprises 1-90% by weight, more preferably at most 5-85% by weight, more preferably at most 8-80% by weight, more preferably at most 11-75% by weight, more preferably at most 13-70% by weight. In a particularly preferred embodiment, the functional layer comprises 21-65% by weight of PEG silane. If the percentage of PEG-silane is too low, the optical fibers will be less tightly packed together, for example in a fiber optic bundle. If the percentage of PEG-silane is too high, the optical fibers will be less tightly packed together, for example in a fiber optic bundle. Furthermore, if the percentage of PEG-silane is too low, the chemical stability of the optical fibers will be reduced. If the percentage of PEG-silane is too high, the optical fibers will tend to stick together too much and will be less smooth, which will cause microcracks and breaks to form more quickly.
[0051] In certain embodiments, the mass fraction of the alkylsilane and / or PEG silane exceeds the mass fraction of the functional silane. In certain embodiments, the mass fraction of the alkylsilane and / or PEG silane exceeds the mass fraction of the functional silane by at least 1.05 times, more preferably 1.1 times, more preferably 1.2 times, more preferably 1.3 times, more preferably 1.4 times, more preferably 1.5 times, more preferably 1.6 times. Preferably, the mass fraction of the alkylsilane and / or PEG silane exceeds the mass fraction of the functional silane by at most 100 times, even at most 80 times, even at most 60 times, even at most 40 times, even at most 30 times, even at most 20 times, even at most 10 times.
[0052] In another embodiment, the mass fraction of the functional silane exceeds the mass fraction of the alkyl silane and / or PEG silane. In one embodiment, the mass fraction of the functional silane exceeds the mass fraction of the alkyl silane and / or PEG silane by at least 1.05 times, more preferably 1.1 times, more preferably 1.2 times, more preferably 1.3 times, more preferably 1.4 times, more preferably 1.5 times, more preferably 1.6 times. Preferably, the mass fraction of the functional silane exceeds the mass fraction of the alkyl silane and / or PEG silane by at most 100 times, even at most 80 times, even at most 60 times, even at most 40 times, even at most 30 times, even at most 20 times, even at most 10 times.
[0053] In one embodiment, the functional layer comprises the following compounds: [Table 1]
[0054] In one embodiment, the functional layer comprises the following compounds: [Table 2]
[0055] In a further embodiment, the functional layer comprises the following compounds: [Table 3]
[0056] In one embodiment, the functional layer comprises the following compounds: [Table 4]
[0057] In one embodiment, the functional layer comprises the following compounds: [Table 5]
[0058] In a further embodiment, the functional layer comprises the following compounds: [Table 6]
[0059] Preferably, the functional layer comprises at least one fatty acid instead of or in addition to at least one of the silanes. The fatty acid can be a saturated or unsaturated fatty acid. In a particularly preferred embodiment, the fatty acid is a saturated fatty acid. The fatty acid improves the mechanical stability of the optical fiber and reduces friction between the optical fibers. Furthermore, the fatty acid can form a hydrophobic protective layer around the fiber.
[0060] Preferably, the fatty acid has a chain length of at least 10 carbon atoms, more preferably at least 11, more preferably at least 12, more preferably at least 13, more preferably at least 14, more preferably at least 15, more preferably at least 16. Preferably, the fatty acid has a chain length of at most 40 carbon atoms, more preferably at most 35, more preferably at most 30, more preferably at most 28, more preferably at most 26, more preferably at most 24, more preferably at most 22. In a preferred embodiment, the fatty acid has a chain length of 10-40 carbon atoms, more preferably 11-35, more preferably 12-30, more preferably 13-28. In a particularly preferred embodiment, the fatty acid has a chain length of 14-22 carbon atoms. If the chain length is too short, the adhesion of the functional layer to the surface of the cladding layer is reduced. If the chain length is too long, the optical fibers tend to adhere too much to each other.
[0061] Preferably, the fatty acid has a melting point of at least 35°C, more preferably at least 39°C, more preferably at least 42°C, more preferably at least 48°C, more preferably at least 52°C, more preferably at least 54°C, more preferably at least 56°C, more preferably at least 58°C, more preferably at least 60°C, more preferably at least 65°C, more preferably at least 70°C. Preferably, the fatty acid has a melting point of at most 180°C, more preferably at most 160°C, more preferably at most 140°C, more preferably at most 120°C, more preferably at most 100°C, more preferably at most 95°C, more preferably at most 90°C. Preferably, the fatty acid has a melting point of 35°C to 180°C, 39°C to 160°C, or 42°C to 100°C. In a particularly preferred embodiment, the fatty acid has a melting point of 53°C to 90°C. If the melting point of the fatty acid is too low, the adhesion of the functional layer to the optical fiber is reduced. This reduces the protection of the optical fiber against, for example, microcracks and breakage. If the melting point of the fatty acid is too high, the optical fibers will stick to each other too much. This will reduce the smoothness and will cause microcracks and breaks when the bending load increases and increases. Preferably, the fatty acid has a boiling point of at least 200°C, more preferably at least 220°C, more preferably at least 240°C, more preferably at least 260°C, more preferably at least 280°C, more preferably at least 300°C. Preferably, the fatty acid has a boiling point of up to 500°C, more preferably up to 400°C, more preferably up to 380°C, more preferably up to 330°C. Preferably, the fatty acid has a boiling point of 200°C to 500°C, 220°C to 400°C or 240°C to 380°C. Examples of fatty acids that can be used according to the invention are capric acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid and arachidic acid.
[0062] In certain embodiments, the functional layer comprises multiple fatty acids, hi certain embodiments, the functional layer comprises at least two fatty acids, at least three fatty acids, or at least four fatty acids.
[0063] Preferably, the majority of the fatty acids have a melting point of at least 35°C, more preferably at least 39°C, more preferably at least 42°C, more preferably at least 48°C, more preferably at least 52°C, more preferably at least 54°C, more preferably at least 56°C, more preferably at least 58°C, more preferably at least 60°C, more preferably at least 65°C, more preferably at least 70°C. Preferably, the majority of the fatty acids, in the form of their mixtures, have a melting point of at most 180°C, more preferably at most 160°C, more preferably at most 140°C, more preferably at most 120°C, more preferably at most 100°C, more preferably at most 95°C, more preferably at most 90°C. Preferably, the majority of the fatty acids, as a mixture, have a melting point of 35°C to 180°C, 39°C to 160°C, or 42°C to 140°C. The melting point as a mixture refers to the melting point that the mixture of the individual fatty acids forming the majority of the fatty acids has in the ratio in which they are used. If the melting point of most fatty acids is too low, the adhesion of the functional layer to the optical fiber is reduced, which reduces the protection of the optical fiber against, for example, microcracks and breakage. If the melting point of most fatty acids is too high, the optical fibers stick to each other too much, which reduces the smoothness and causes microcracks and breakage when the bending load increases and increases.
[0064] Preferably, the functional layer comprises one or more fatty acids in a proportion of at least 1% by weight, more preferably at least 2% by weight, more preferably at least 3% by weight, more preferably at least 4% by weight, more preferably at least 5% by weight, more preferably at least 6% by weight, more preferably at least 7% by weight. Preferably, the functional layer comprises at least one fatty acid in a proportion of up to 85% by weight, more preferably at most 80% by weight, more preferably at most 75% by weight, more preferably at most 70% by weight, more preferably at most 65% by weight, more preferably at most 60% by weight, more preferably at most 56% by weight. In a preferred embodiment, the functional layer comprises at least one fatty acid in a proportion of 1-85% by weight, more preferably 2-80% by weight, more preferably 3-75% by weight, more preferably 4-70% by weight. In a particularly preferred embodiment, the functional layer comprises one or more fatty acids in a proportion of 7-56% by weight in total. If the proportion of the at least one fatty acid is too low, the optical fibers will not slide easily against each other. If the proportion of the at least one fatty acid is too high, the optical fibers will adhere to each other.
[0065] In one embodiment, the functional layer comprises the following compounds: [Table 7]
[0066] In one embodiment, the functional layer comprises the following compounds: [Table 8]
[0067] In one embodiment, the functional layer comprises the following compounds: [Table 9]
[0068] In one embodiment, the functional layer comprises the following compounds: [Table 10]
[0069] In one embodiment, the functional layer comprises the following compounds: [Table 11]
[0070] In one embodiment, the functional layer comprises the following compounds: [Table 12]
[0071] In an embodiment, the functional layer comprises at least one polyhydric alcohol instead of or in addition to at least one of the silanes. The polyhydric alcohol according to the invention is glycerol, diethylene glycol or 1,5-pentanediol, as well as alkane polyols such as alkane diols and alkane triols, in particular alkane polyols with a chain length of 2 to 10 carbon atoms, preferably 3 to 8 carbon atoms. Preferably, the functional layer comprises at least one polyhydric alcohol in a proportion of at least 3% by weight, more preferably at least 5% by weight, more preferably at least 10% by weight, more preferably at least 15% by weight, more preferably at least 20% by weight, more preferably at least 25% by weight, more preferably at least 30% by weight. Preferably, the functional layer comprises at least one polyhydric alcohol in a proportion of up to 90% by weight, more preferably up to 87% by weight, more preferably up to 84% by weight, more preferably up to 81% by weight, more preferably up to 79% by weight, more preferably up to 77% by weight, more preferably up to 75% by weight. In a preferred embodiment, the functional layer comprises 3-90% by weight of polyhydric alcohol, more preferably 5-87% by weight, more preferably 10-84% by weight, more preferably 15-81% by weight. In a particularly preferred embodiment, the functional layer comprises 30-75% by weight of polyhydric alcohol. Polyhydric alcohols improve the sliding of optical fibers against each other, thereby reducing the occurrence of microcracks and breaks. Polyhydric alcohols improve the handleability, packing density and reseparability of optical fibers, for example in optical fiber bundles, and in particular polyhydric alcohols provide the desired "wetting behavior", i.e. the property of the fiber article behaving like a wet fiber article.
[0072] The functional layer may contain at least one polyalkylene oxide instead of or in addition to at least one of the silanes. The polyalkylene oxides according to the invention are in particular polyglycols, such as polyethylene glycol and polypropylene glycol, as well as other polyalkylene oxides from monomers having 2 to 6 carbon atoms. Preferably, the functional layer contains at least one polyalkylene oxide in a proportion of at least 2% by weight, more preferably at least 3% by weight, more preferably at least 4% by weight, more preferably at least 5% by weight, more preferably at least 6% by weight, more preferably at least 7% by weight, more preferably at least 8% by weight. Preferably, the functional layer contains at least one polyalkylene oxide in a proportion of up to 90% by weight, more preferably up to 85% by weight, more preferably up to 80% by weight, more preferably up to 75% by weight, more preferably up to 70% by weight, more preferably up to 68% by weight, more preferably up to 65% by weight. In a preferred embodiment, the functional layer contains at least one polyalkylene oxide in an amount of 1 to 90% by weight, more preferably 2 to 85% by weight, more preferably 3 to 80% by weight, and even more preferably 4 to 75% by weight. In a particularly preferred embodiment, the functional layer contains the polyalkylene oxide in an amount of 8 to 65% by weight. The polyalkylene oxide reduces friction between optical fibers and improves the mechanical stability of the optical fiber. The polyalkylene oxide further improves the cohesion of the optical fibers, for example in an optical fiber bundle.
[0073] In a preferred embodiment, the polyalkylene oxide has a chain length of at least 3, more preferably at least 4, more preferably at least 5, more preferably at least 6, more preferably at least 7, and more preferably at least 8 alkylene oxide units. Preferably, the polyalkylene oxide has a chain length of at most 100, more preferably at most 75, more preferably at most 50, more preferably at most 20, and more preferably at most 14 alkylene oxide units. In an embodiment, the polyalkylene oxide has a chain length of 3 to 100, more preferably 4 to 50, and more preferably 6 to 20 alkylene oxide units. In a particularly preferred embodiment, the polyalkylene oxide has a chain length of 7 to 14 alkylene oxide units. It is advantageous to use a polyalkylene oxide that is liquid at room temperature (20° C., 1013 hPa).
[0074] In one embodiment, the functional layer comprises the following compounds: [Table 13]
[0075] In one embodiment, the functional layer comprises the following compounds: [Table 14]
[0076] In one embodiment, the functional layer comprises the following compounds: [Table 15]
[0077] In one embodiment, the functional layer comprises the following compounds: [Table 16]
[0078] In one embodiment, the functional layer comprises the following compounds: [Table 17]
[0079] In one embodiment, the functional layer comprises the following compounds: [Table 18]
[0080] In one embodiment, the functional layer comprises the following compounds: [Table 19]
[0081] In one embodiment, the functional layer comprises the following compounds: [Table 20]
[0082] In one embodiment, the functional layer comprises the following compounds: [Table 21]
[0083] The IR spectrum of the functional layer can be recorded by pressing an ATR crystal against the functional layer. The spectrum is recorded in ATR mode, so that the spectrum of the fiber corresponds to the spectrum of the functional layer. The functional layer exhibits a characteristic absorption in the infrared range of the Fourier-transform-Infrared-Attenuated-Total-Reflection (FTIR-ATR) spectrum. The IR spectra of the functional layer on the fiber of the fiber article of the invention are characteristic due to their unique composition. In particular, they differ from the IR spectra of functional layers in the prior art. For example, the functional layer of the invention exhibits no IR spectrum at 1750 cm, if any at all. -1 (±25cm-1 ), which is due to the favorable absence of polyacrylates and polymethacrylates. The same can be seen in the -1 (±25cm -1 ) band, which is due to the favorable absence of aromatic components. Many aromatic compounds are undesirable because they are carcinogenic.
[0084] Preferably, the functional layer has a peak at 3800 cm in the FTIR-ATR spectrum. -1 ~4000cm -1 Maximum absorption band height in the range of 3200 cm -1 ~3600cm -1 Preferably, the functional layer has a ratio of maximum absorption band heights in the range of 3800 cm to 3800 cm in the FTIR-ATR spectrum of at least 1.3, more preferably at least 1.4, more preferably at least 1.5, more preferably at least 1.6, more preferably at least 1.7, more preferably at least 1.8, more preferably at least 1.9, more preferably at least 2.0, more preferably at least 2.1, and more preferably at least 2.2. -1 ~4000cm -1 Maximum absorption band height in the range of 3200 cm -1 ~3600cm -1 is at most 35, more preferably at most 30, more preferably at most 25, more preferably at most 20, more preferably at most 15, more preferably at most 10, more preferably at most 9, more preferably at most 8, more preferably at most 7, and more preferably at most 6. Preferably, the functional layer has a maximum absorption band height ratio of 3800 cm in the FTIR-ATR spectrum. -1 ~4000cm -1 Maximum absorption band height in the range of 3200 cm -1 ~3600cm -1The ratio of the maximum absorption band heights in the range of 3200 cm to 35, more preferably 1.4 to 30, more preferably 1.5 to 25, more preferably 1.6 to 6. The absorptions described herein are brought about, for example, by advantageous ratios of the functional silane and / or optional polyhydric alcohol to further components of the functional layer. -1 ~3600cm -1 If the relative absorption of the 3200 cm-1 as described herein is too low, the ratio of functional silane to other components of the functional layer is too low. This leads to poor adhesion of the functional layer to the surface of the cladding layer. Furthermore, the adhesion of the functional layer to further layers, such as adhesive layers, for example in a composite of optical fiber bundles, is reduced. -1 ~3600cm -1 If the relative absorption is too high, the ratio of functional silane to other components of the functional layer is too high, which increases friction between the optical fibers and reduces lubricity.
[0085] Preferably, the functional layer has a peak at 1500 cm in the FTIR-ATR spectrum. -1 ~1900cm -1 Maximum absorption band height in the range of 800 cm -1 ~1200cm -1 Preferably, the functional layer has a ratio of maximum absorption band heights in the range of 1500 cm to 1500 cm in the FTIR-ATR spectrum of at least 1.1, more preferably at least 1.2, more preferably at least 1.3, more preferably at least 1.4, more preferably at least 1.5, more preferably at least 1.6, more preferably at least 1.7, more preferably at least 1.8, more preferably at least 1.9, and more preferably at least 2.0. -1 ~1900cm -1 Maximum absorption band height in the range of 800 cm -1 ~1200cm -1is at most 300, more preferably at most 200, more preferably at most 100, more preferably at most 50, more preferably at most 30, more preferably at most 20, more preferably at most 10, more preferably at most 7, more preferably at most 6, and more preferably at most 5. Preferably, the functional layer has a maximum absorption band height ratio of 1500 cm in the FTIR-ATR spectrum. -1 ~1900cm -1 The ratio of the maximum absorption band height in the range of 800 nm to 1200 nm to the maximum absorption band height in the range of 1.3 to 300, more preferably 1.4 to 250, more preferably 1.5 to 200, more preferably 2.0 to 10. The absorptions described herein are, for example, in particular due to advantageous ratios of functional silane, optional alkyl silane and / or optional PEG silane to undesired photopolymerizable or photopolymerized compounds. -1 ~1200cm -1 If the relative absorption of is too low, the ratio of photopolymerizable or photopolymerized compounds is too high. Such a functional layer has serious health implications.
[0086] Preferably, the functional layer has a peak at 1500 cm in the FTIR-ATR spectrum. -1 ~1900cm -1 Maximum absorption band height in the range of 2700 cm -1 ~3000cm -1 Preferably, the functional layer has a ratio of maximum absorption band heights in the range of 1500 cm to 1500 cm in the FTIR-ATR spectrum of at least 1.1, more preferably at least 1.2, more preferably at least 1.3, more preferably at least 1.4, more preferably at least 1.5, more preferably at least 1.6, more preferably at least 1.7, more preferably at least 1.8, more preferably at least 1.9, and more preferably at least 2.0. -1 ~1900cm -1 Maximum absorption band height in the range of 2700 cm -1 ~3000cm -1The ratio of the maximum absorption band height in the range of 1500 nm to 1900 nm in the FTIR-ATR spectrum is preferably at most 300, more preferably at most 200, more preferably at most 100, more preferably at most 50, more preferably at most 30, more preferably at most 20, more preferably at most 10, more preferably at most 7, more preferably at most 6, and more preferably at most 5. Preferably, the functional layer has a ratio of the maximum absorption band height of 2700 cm to the maximum absorption band height in the range of 1500 nm to 1900 nm in the FTIR-ATR spectrum. -1 ~3000cm -1 The ratio of the maximum absorption band heights in the range of 2700 cm to 300, more preferably 1.4 to 250, more preferably 1.5 to 200, and even more preferably 2.0 to 5. The absorptions described herein are, for example, in particular due to advantageous ratios of functional silane, optional alkyl silane, optional PEG silane and / or optional fatty acid to undesired photopolymerizable or photopolymerized compounds. -1 ~3000cm -1 If the relative absorption of is too low, the ratio of photopolymerizable or photopolymerized compounds is too high, such a functional layer may have serious health implications and may cause health hazards to the patient.
[0087] Preferably, the functional layer has a peak at 1500 cm in the FTIR-ATR spectrum. -1 ~1900cm -1 Maximum absorption band height in the range of 3200 cm -1 ~3600cm -1 The ratio of the maximum absorption band height in the range of 1500 nm to 1900 nm in the FTIR-ATR spectrum of 3200 cm to 3200 cm is preferably at least 1.1, more preferably at least 1.2, more preferably at least 1.3, more preferably at least 1.4, and more preferably at least 1.5. -1 ~3600cm -1Preferably, the functional layer has a ratio of the maximum absorption band height in the range of 1500 cm to 3.0, more preferably a ratio of the maximum absorption band height in the range of 1500 cm to 2.5, more preferably a ratio of the maximum absorption band height in the range of 1500 cm to 2.2, and more preferably a ratio of the maximum absorption band height in the range of 1500 cm to 2.0. -1 ~1900cm -1 Maximum absorption band height in the range of 3200 cm -1 ~3600cm -1 The ratio of the maximum absorption band heights in the range of 3200 cm to 3200 cm is preferably 1.1 to 3, more preferably 1.1 to 2.5, and even more preferably 1.1 to 2.0 or 1.2 to 2.5. The absorptions described herein are, for example, particularly due to advantageous ratios of functional silane and / or optional polyhydric alcohol to undesired photopolymerizable or photopolymerized compounds. -1 ~3600cm -1 If the relative absorption of is too low, the ratio of photopolymerizable or photopolymerized compounds is too high. Such a functional layer has serious health implications.
[0088] Preferably, the functional layer has a peak at 2700 cm in the FTIR-ATR spectrum. -1 ~3000cm -1 Maximum absorption band height in the range of 800 cm -1 ~1200cm -1 Preferably, the functional layer has a ratio of maximum absorption band heights in the range of 3200 cm to 3200 cm in the FTIR-ATR spectrum of at least 1.1, more preferably at least 1.2, more preferably at least 1.3, and more preferably at least 1.4. -1 ~3600cm -1 Maximum absorption band height in the range of 800 cm -1 ~1200cm -1 is at most 35, more preferably at most 30, more preferably at most 25, more preferably at most 20, more preferably at most 15, more preferably at most 10, more preferably at most 9.0, more preferably at most 5, more preferably at most 3.0, and more preferably at most 2.0. Preferably, the functional layer has a maximum absorption band height ratio of 3200 cm in the FTIR-ATR spectrum.-1 ~3600cm -1 Maximum absorption band height in the range of 800 cm -1 ~1200cm -1 The ratio of the maximum absorption band heights in the range of 800 nm to 1200 nm is 1.1 to 35, more preferably 1.2 to 15, and even more preferably 1.3 to 2.0. The absorptions described herein are, for example, due to advantageous ratios of functional silanes and / or any polyhydric alcohols to functional silanes, any alkyl silanes and / or any PEG silanes, in particular. If the relative absorption from 800 nm to 1200 nm described herein is too low, the ratio of functional silanes is too low ... -1 ~1200cm -1 If the relative absorption is too high, the ratio of functional silanes is too high.
[0089] In order for the optical fibers to have a good sliding effect between them without adhering to each other, the functional layer should have an appropriate coefficient of friction. The coefficient of friction can be measured on the surface of the functional layer by methods known to those skilled in the art. This can be done, for example, by displacing an optical fiber article or a corresponding glass rod from the same material as the fiber article (test article) at an angle of 90° against a friction partner (Reibpartner) also formed from an optical fiber article or a corresponding glass rod at a speed of 10 mm / min with a normal force Fn of 0.5 N. Displace longitudinally relative to the test article. The friction partner is likewise formed from an optical fiber article or a corresponding glass rod. Here, a friction force occurs according to the friction value (Reibwert), which is determined as a measure of the friction value (friction value=quotient from friction force and normal force). Preferably, the functional layer has a coefficient of friction of at most 0.5, more preferably at most 0.45, more preferably at most 0.35, more preferably at most 0.3, more preferably at most 0.2, more preferably at most 0.15. Preferably, the functional layer has a coefficient of friction of at least 0.001, more preferably at least 0.01, more preferably at least 0.03, and even more preferably at least 0.05. In a preferred embodiment, the functional layer has a coefficient of friction of 0.001 to 0.5, more preferably 0.01 to 0.35, and even more preferably 0.03 to 0.2. In a particularly preferred embodiment, the functional layer has a coefficient of friction of less than 0.2. If the coefficient of friction is too high, the optical fibers will not slide easily against each other, resulting in microcracks and breakage. If the coefficient of friction is too low, the optical fibers will not be easily held together, for example in an optical fiber bundle.
[0090] The surface of the functional layer should have a suitable contact angle, for example in order to achieve good wetting of the optical fibers by the adhesive, for example in the composite of the optical fiber bundle. The contact angle can be measured on the surface of the functional layer by methods known to the skilled person (for example according to ISO DIN 55660-2:2011). Preferably, the functional layer has a contact angle of at least 10°, more preferably at least 20°, more preferably at least 40°, more preferably at least 60°, more preferably at least 80°. Preferably, the functional layer has a contact angle of up to 125°, more preferably at most 100°, in a preferred embodiment, the functional layer has a contact angle of 20° to 120°, more preferably 40° to 100°, more preferably 60° to 100°. In a particularly preferred embodiment, the functional layer has a contact angle of 50° to 85°. If the contact angle is too small, the surface of the functional layer becomes too hydrophilic, and the chemical protection action is reduced. If the contact angle is too large, the wettability of the surface of the functional layer by, for example, the adhesive layer in the composite is reduced.
[0091] The functional layer should adhere well to the surface of the fiber, allow good but limited adhesion of the fiber, and allow good adhesion of the fiber article, in particular the fiber bundle, to other materials, for example sleeves. The results obtained in the extrusion test described below are a measure of the adhesion between the fibers. In the extrusion test, a fiber bundle, or possibly different fiber bundles with a diameter of 5 mm for comparison, are each glued into a stainless steel sleeve with the same adhesive, for example with a two-component epoxy resin adhesive that is preferably solvent-free and crosslinks at room temperature (e.g. Araldit AY103-1 hardener; REN HY 956, Huntsman; cured at 60° C. for 2 hours). The end faces of the fiber bundles are ground and polished. The extrusion forces are then determined at least qualitatively or relative to each other with a test mandrel with a round cross section, a diameter of 2.5 mm, and a flat end face, by pressing the test mandrel in the fiber direction against the fibers glued in the sleeve. The extrusion speed is 6 mm / min. There are two failure patterns. In the first case, the adhesion of the fiber bundle to the stainless steel sleeve is broken (the entire fiber bundle is pushed out of the sleeve). In the second case, the adhesion between the fibers is broken. In the first case, the adhesion between the fibers is better than the adhesion of the fiber bundle to the stainless steel sleeve. For the second case, this suggests a lack of adhesive on the glass fiber, which indicates a poor adhesion promotion of the functional layer. The maximum detected force required to displace the bonded fiber bundle under the test mandrel from the stainless steel sleeve or the surrounding fibers is the extrusion force.
[0092] Preferably, the optical fiber article has a pushing force of at least 250N, more preferably at least 300N, more preferably at least 350N, more preferably at least 400N, more preferably at least 500N, at least 700N or at least 900N. In an embodiment, the optical fiber article has a pushing force of up to 5,000N, more preferably up to 4,500N, more preferably up to 4,000N, more preferably up to 3,500N, more preferably up to 3,000N. In a preferred embodiment, the optical fiber article has a pushing force of 100-5,000N, more preferably 150-4,500N, more preferably 200-4,000N. If the pushing force is too low, the functional layer does not adhere well to the surface of the cladding layer or the adhesion promotion of the functional layer is too weak.
[0093] Preferably, the optical fiber article has a fiber with a high breaking length, in particular of at least 20 m. More preferably, the fiber has a breaking length of at least 30 m, more preferably at least 40 m, more preferably at least 50 m, more preferably at least 60 m, more preferably at least 70 m, more preferably at least 80 m, more preferably at least 90 meters. If this length is too short, the optical fiber breaks too frequently and is unsuitable for use as a light guide and / or image guide. Furthermore, health risks arise from broken optical fibers. The breaking length can be measured as follows: The test fiber is provided as a continuous fiber with a length of at least 2 km on a spool (for example a standard polystyrene foam spool with a circumference of 0.49 m). A defined bending load is applied to the test fiber by a tension bending apparatus, whereby the fiber is rewound by four rollers with a radius of 6 mm. The test fiber, now under constant stress, is unwound from the braked spool and wound onto a second motor-driven spool. If fiber break occurs, the unwinding process is stopped by a break sensor. The fiber is repositioned to continue the measurement. The break length is the fiber length at which the break probability is 63% (Weibull distribution). For the calculation, preferably at least 10 measurements are performed, preferably 25 measurements. The test is performed with a tension of 25+ / -1 cN and a rewind speed of 25+ / -1 rpm (corresponding to 12.5 m / min).
[0094] Fiber-optic articles should contain fibers that are mechanically stable and, if possible, do not break. The tendency of a fiber to break can be measured in a breaking loop test according to DIN 58141-6:2011. This test is used to determine the basic strength of a fiber article. In this method, the mechanical bending radius of light guide fibers is determined by loading these light guide fibers with a narrowing 360° loop until fiber breakage occurs (breaking test). The result of the breaking loop test is the bending radius, i.e. a measure of how far the fiber can be bent without breaking. The fibers of the fiber-optic article preferably have a bending radius of less than 10 mm, in particular less than 5 mm, less than 3 mm or even less than 2 mm. These fibers have a very small bending radius, especially after hydrolytic loading. Thus, the bending radius of the fiber preferably remains less than 12 mm, less than 8 mm or less than 6 mm, even after storing the fiber in water at 50° C. for 5 days. The fact that these fibers largely retain their good bending properties even under hydrolytic loading is a major advantage with respect to cleaning and sterilization of fiber optic articles.
[0095] Acrylates, methacrylates, vinyl and styrene compounds, as well as other unsaturated compounds that cure under UV radiation, can be harmful to the environment and can pose health hazards to humans, therefore the functional layer should have as low a proportion of photopolymerizable and / or photopolymerized substances as possible.
[0096] Preferably, the optical fiber article has a photopolymerized polymer content in the functional layer of less than 1% by weight, more preferably less than 4% by weight, more preferably less than 3% by weight, more preferably less than 2% by weight, more preferably less than 1% by weight, more preferably less than 0.8% by weight, more preferably less than 0.6% by weight, more preferably less than 0.4% by weight, more preferably less than 0.2% by weight, more preferably less than 0.1% by weight, more preferably less than 0.05% by weight, more preferably less than 0.01% by weight, more preferably less than 0.005% by weight, more preferably less than 0.001% by weight. In a particularly preferred embodiment, the functional layer does not contain a photopolymerized polymer. "Photopolymerized polymer" refers to a polymer that can be produced by polymerizing a UV-curable monomer or oligomer. Photopolymerized polymers that are preferably avoided in the present invention are, for example, polyacrylates, polymethacrylates, polyvinyl polymers, polystyrene and / or derivatives thereof. If the proportion of photopolymerized polymer in the functional layer is too high, the optical fiber article may pose a potential health risk. In particular, in medical devices that are frequently autoclaved, the photopolymerized polymer may release residual monomers or photoinitiators. Therefore, in particular in medical devices that come into contact with human organs, such as endoscopes, the proportion of photopolymerized polymer should not be higher than described here. In particular, the content of photopolymerizable monomers and / or oligomers in the functional layer is also low. In particular, the content of acrylates, methacrylates, styrene compounds and vinyl compounds in the functional layer is preferably limited to less than 1% by weight, less than 0.1% by weight or less than 0.01% by weight.
[0097] Photoinitiators may be harmful to human health. In a preferred embodiment, the optical fiber article has a content of photoinitiators and / or derivatives thereof in the functional layer of less than 5% by weight, more preferably less than 4% by weight, more preferably less than 3% by weight, more preferably less than 2% by weight, more preferably less than 1% by weight, more preferably less than 0.8% by weight, more preferably less than 0.6% by weight, more preferably less than 0.4% by weight, even more preferably less than 0.2% by weight, more preferably less than 0.1% by weight, more preferably less than 0.05% by weight, more preferably less than 0.01% by weight, more preferably less than 0.005% by weight, even more preferably less than 0.001% by weight. In a particularly preferred embodiment, the functional layer does not contain photoinitiators and / or derivatives thereof. "Photoinitiators and / or derivatives thereof" refers to chemical compounds that form reactive species after absorption of photons, e.g. UV light, that can initiate a reaction, e.g. polymerization. Photoinitiators and / or derivatives thereof may also refer to those compounds that have already reacted. The photoinitiator according to the present invention is, for example, a radical photoinitiator, a cationic photoinitiator and / or a thermal latent photoinitiator. Such photoinitiators are, for example, acylphosphine oxides, alpha-alkoxy-arylketones or aryldiazoniums or combinations thereof. If the proportion of photoinitiator and / or its derivatives in the functional layer is too high, the optical fiber article may pose a health risk. This is particularly undesirable in medical devices.
[0098] The functional layer should be sufficiently dry and have a low water content. Preferably, the optical fiber article has a residual amount of water in the functional layer of less than 5% by weight, more preferably less than 4% by weight, more preferably less than 3% by weight, more preferably less than 2% by weight, more preferably less than 1% by weight, more preferably less than 0.8% by weight, more preferably less than 0.6% by weight, more preferably less than 0.4% by weight, even more preferably less than 0.2% by weight, more preferably less than 0.1% by weight, more preferably less than 0.05% by weight, more preferably less than 0.01% by weight, more preferably less than 0.005% by weight, even more preferably less than 0.001% by weight. In a particularly preferred embodiment, the functional layer does not contain water. If the proportion of water is too high, the insulating protective effect of the functional layer is reduced and the mechanical and chemical stability of the optical fiber article is reduced.
[0099] The functional layer should be sufficiently dry and have a low residual amount of water-miscible solvent. Such solvents are in particular aliphatic ethers or alcohols with up to 10 carbon atoms and / or carboxylic acids with up to 6 carbon atoms. Examples of water-miscible solvents according to the invention are acetic acid, ethanol, isopropanol, dipropylene glycol monomethyl ether or tripropylene glycol monomethyl ether. Preferably, the optical fiber article has a residual amount of water-miscible solvent in the functional layer of less than 5% by weight, more preferably less than 4% by weight, more preferably less than 3% by weight, more preferably less than 2% by weight, more preferably less than 1% by weight, more preferably less than 0.8% by weight, more preferably less than 0.6% by weight, more preferably less than 0.4% by weight, even more preferably less than 0.2% by weight, more preferably less than 0.1% by weight, more preferably less than 0.05% by weight, more preferably less than 0.01% by weight, more preferably less than 0.005% by weight, more preferably less than 0.001% by weight. In a particularly preferred embodiment, the functional layer is free of water-miscible solvents: too high a proportion of water-miscible solvents reduces the insulating protective effect of the functional layer and reduces the mechanical and chemical stability of the optical fiber article.
[0100] In a particularly preferred embodiment, the optical fiber article has a residual amount of short-chain carboxylic acids having up to 10 carbon atoms in the functional layer of less than 5% by weight, more preferably less than 4% by weight, more preferably less than 3% by weight, more preferably less than 2% by weight, more preferably less than 1% by weight, more preferably less than 0.8% by weight, more preferably less than 0.6% by weight, more preferably less than 0.4% by weight, even more preferably less than 0.2% by weight, more preferably less than 0.1% by weight, more preferably less than 0.05% by weight, more preferably less than 0.01% by weight, more preferably less than 0.005% by weight, even more preferably less than 0.001% by weight. Such short-chain carboxylic acids are, for example, acetic acid or citric acid. In a particularly preferred embodiment, the functional layer does not contain short-chain carboxylic acids having up to 10 carbon atoms.
[0101] In a particularly preferred embodiment, the optical fiber article has a residual amount of fatty acid alcohols having up to 4 carbon atoms in the functional layer of less than 5% by weight, more preferably less than 4% by weight, more preferably less than 3% by weight, more preferably less than 2% by weight, more preferably less than 1% by weight, more preferably less than 0.8% by weight, more preferably less than 0.6% by weight, more preferably less than 0.4% by weight, even more preferably less than 0.2% by weight, more preferably less than 0.1% by weight, more preferably less than 0.05% by weight, more preferably less than 0.01% by weight, more preferably less than 0.005% by weight, even more preferably less than 0.001% by weight. Such short-chain carboxylic acids are, for example, ethanol or isopropanol. In a particularly preferred embodiment, the functional layer does not contain fatty alcohols having up to 4 carbon atoms.
[0102] The optical fiber article should be well suited for use in medical devices, such as endoscopes. For medical applications, the optical fiber article should be as durable as possible even when autoclaved frequently. For this purpose, it is important that the optical fiber article has as little halogen as possible. Preferably, the optical fiber article has a halogen content in the functional layer of less than 500 ppm (m / m), more preferably less than 400 ppm (m / m), more preferably less than 300 ppm (m / m), more preferably less than 250 ppm (m / m), more preferably less than 200 ppm (m / m), more preferably less than 150 ppm (m / m), more preferably less than 100 ppm (m / m), more preferably less than 80 ppm (m / m), more preferably less than 60 ppm (m / m), more preferably less than 40 ppm (m / m), more preferably less than 20 ppm (m / m), and even more preferably less than 10 ppm (m / m). In a particularly preferred embodiment, the functional layer does not contain halogens. The halogens are, for example, chlorine, fluorine, bromine and / or iodine or their anions. The term "halogen" includes in particular halides, preferably also other halogen compounds. If the concentration of halogens in the functional layer is too high, in particular in the case of, for example, steam sterilization, the corresponding halogen acids are formed. The corresponding halogen acids reduce the durability of the optical fiber article and can leak out of the optical fiber article. In particular, halogen acids attack materials such as, for example, stainless steel of autoclaves and endoscopes, forming undesirable rust.
[0103] In particular, residual amounts of chloride in the functional layer may lead to the formation of hydrochloric acid. Therefore, the optical fiber article should have as little chloride as possible. Preferably, the optical fiber article has a chloride content in the functional layer of less than 500 ppm (m / m), more preferably less than 400 ppm (m / m), more preferably less than 300 ppm (m / m), more preferably less than 250 ppm (m / m), more preferably less than 200 ppm (m / m), more preferably less than 150 ppm (m / m), more preferably less than 100 ppm (m / m), more preferably less than 80 ppm (m / m), more preferably less than 60 ppm (m / m), more preferably less than 40 ppm (m / m), more preferably less than 20 ppm (m / m), and even more preferably less than 10 ppm (m / m). In a particularly preferred embodiment, the functional layer does not contain chloride. If the chloride content is too high, the corrosion resistance of the optical fiber article is reduced.
[0104] For an optical glass fiber article to be suitable for medical or diagnostic applications, the optical glass fiber article should be biocompatible. Preferably, the fiber article is biocompatible according to ISO 10993-1:2018. Preferably, the optical fiber article is biocompatible in cytotoxicity testing according to ISO 10993-5:2009.
[0105] The fiber optic article is preferably biocompatible according to ISO 10993-1:2018 and / or ISO 10993-5:2009. The fiber optic article is preferably biocompatible according to USP Class VI.
[0106] Fiber optic articles should contain, as far as possible, only compounds that are not dangerous to human health. For example, humans also come into contact with fiber optic articles during their manufacture and processing. Preferably, fiber optic articles contain no more than a maximum permissible workplace concentration (MAK value) of 240 mg in the functional layer. * m -3The proportion of compounds less than 5% by weight, based on the mass of the functional layer, is more preferably less than 4% by weight, even more preferably less than 3% by weight, even more preferably less than 2% by weight, even more preferably less than 1% by weight, even more preferably less than 0.8% by weight, even more preferably less than 0.6% by weight, even more preferably less than 0.4% by weight, even more preferably less than 0.2% by weight, even more preferably less than 0.1% by weight, even more preferably less than 0.05% by weight, even more preferably less than 0.01% by weight, even more preferably less than 0.005% by weight, and even more preferably less than 0.001% by weight.
[0107] Preferably, the optical fiber comprises a fiber core and a cladding or cladding layer, the functional layer being arranged on the cladding layer. In a preferred embodiment, the core layer consists of a core glass. In another embodiment, the fiber core consists of a core polymer. Suitable core polymers are, for example, polyacrylates, polymethacrylates, polyurethanes, polyesters, polyamides and mixtures thereof. The core glass may be a multicomponent glass, in particular the core glass may have a combination of oxides, i.e. an oxide glass. Quartz glass is also basically suitable as a core glass, but unlike multicomponent glasses it has a very high melting point, which makes processing more difficult and, above all, energy-intensive.
[0108] The optical fiber preferably comprises a cladding layer covering the fiber core. In a preferred embodiment, the cladding layer comprises a cladding glass. The cladding glass may be a multi-component glass, in particular the cladding glass may comprise a combination of oxides, i.e. an oxide glass. In another embodiment, the cladding layer comprises a cladding polymer. Cladding polymers according to the invention are, for example, polyacrylates, polymethacrylates, polyurethanes, polyesters, polyamides and mixtures thereof.
[0109] In certain embodiments, the optical fiber is a quartz fiber. In certain embodiments, the cladding and / or fiber core is at least 76% by weight quartz, more preferably at least 81% by weight, more preferably at least 84% by weight, more preferably at least 88% by weight, more preferably at least 92% by weight, more preferably at least 95% by weight, more preferably at least 97% by weight, more preferably at least 98% by weight. A higher percentage of quartz provides better chemical resistance and better temperature resistance.
[0110] In certain embodiments, the core glass has the following characteristics: Preferably, the core glass has at least 8% by weight of SiO2, more preferably at least 23% by weight, more preferably at least 24% by weight, particularly preferably at least 25% by weight or even at least 26% by weight. In certain embodiments, the core glass may contain at least 28.3% by weight of SiO2, very particularly preferably at least 34% by weight of SiO2. In some preferred embodiments, the core glass contains at least 35% by weight of SiO2, more preferably at least 42% by weight.
[0111] A preferred core glass of the present invention has the following composition in weight percent: [Table 22]
[0112] R2O is the sum of all alkali metal oxide contents.
[0113] One or more of the following components may be included: Cs2O, Rb2O, MgO, CaO, SrO, Gd2O3, Lu2O3, Sc2O3, Y2O3, In2O3, Ga2O3 and WO3.
[0114] The following components should preferably not be contained in the core glass or should only be contained in concentrations resulting from unavoidable impurities of the raw materials: TiO2, CeO2, Nb2O5, MoO3, Bi2O3, PbO, CdO, Tl2O, As2O3, Sb2O3, SO3, SeO2, TeO2, BeO, radioactive elements and coloring components, unless otherwise stated in the text. In particular, TiO2 should be avoided, since this component can lead to significant absorption in the UV range. In a preferred embodiment, the component WO3 is also avoided.
[0115] The components TiO2, CeO2, Nb2O5 and / or Bi2O3 may be contained in the core glass in an amount of up to 0.5% by weight, preferably up to 0.3% by weight, particularly preferably up to 0.2% by weight. In a preferred embodiment, the core glass is free of these components.
[0116] Preferably, the core glass is free of optically active components, in particular Sm2O3, Nd2O3, Dy2O3, Pr2O3, Eu2O3, Yb2O3, Tb2O3, Er2O3, Tm2O3 and / or Ho2O3. Preferred core glasses do not contain CeO2, since CeO2 absorbs in the UV range.
[0117] The content of the alkaline earth metal oxides, La2O3, Ta2O5, ZrO2 and HfO2 components is preferably and especially for core glasses with a refractive index value of more than 1.65, a total of at least 40% by weight, more preferably at least 42% by weight, more preferably at least 50% by weight, and particularly preferably at least 55% by weight. If the content of these components is too low, the desired refractive index is usually not achieved. Depending on the formulation, this total should not exceed a value of 72% by weight.
[0118] In a particular embodiment, the cladding glass has the following characteristics:
[0119] Preferably, the cladding glass has a SiO2 content of more than 60% by weight, more preferably more than 65% by weight, particularly preferably at least 69% by weight. The SiO2 content is preferably up to 75% by weight, particularly preferably up to 73% by weight. The cladding glass tends to be more susceptible to environmental influences than the core glass. A higher SiO2 content confers better chemical resistance. Therefore, the content of this component in the cladding glass is preferably higher than in the core glass.
[0120] The coefficient of thermal expansion (CTE) in the temperature range of 20-300°C may be the same or different for the fiber core and cladding. In particular, the CTEs are different. Preferably, the CTE of the cladding is smaller than the CTE of the fiber core, and preferably the CTE of the cladding is at least 1.0. * 10 -6 / K is smaller or particularly preferably at least 2.5 * 10 -6 / K small. The fiber core preferably has a CTE of 6.5 * 10 -6 ~10 * 10 -6 / K, and the cladding has a CTE of 4.5 * 10 -6 ~6 * 10 -6 / K.
[0121] The following table shows some preferred compositions of cladding glasses that can be used with the core glass. The cladding glasses contain the following (in weight percent on an oxide basis): [Table 23]
[0122] As core and / or cladding glasses, chalcogenide glasses, in particular the glasses disclosed in DE 40 11 553 A1 and EP 0 217 195 A1, are also considered.
[0123] The fiber optic article may comprise one or more optical fibers, where the optical fibers may be randomly present in the composite or arranged in a fiber optic bundle. The fiber optic article may comprise one or more optical fiber bundles, where the optical fiber bundles may be randomly present in the composite or arranged in a fiber bundle group. The fiber optic article may comprise one or more fiber optic bundle groups.
[0124] In embodiments, the optical fiber article comprises at least 1 optical fiber, more preferably at least 2 optical fibers, more preferably at least 3 optical fibers, more preferably at least 5 optical fibers, more preferably at least 7 optical fibers, more preferably at least 9 optical fibers, more preferably at least 10 optical fibers, and more preferably at least 11 optical fibers. In particularly preferred embodiments, the optical fiber article comprises at least 15 optical fibers, more preferably at least 50 optical fibers, more preferably at least 100 optical fibers, more preferably at least 300 optical fibers, more preferably at least 700 optical fibers, more preferably at least 1,600 optical fibers, more preferably at least 2,800 optical fibers, and more preferably at least 4,700 optical fibers.
[0125] The optical fiber bundles may be glued together, for example into a larger composite, and / or embedded in a sleeve. In a preferred embodiment, the optical fiber article does not have an adhesive layer. In one embodiment, the optical fiber article includes, in addition to the functional layer, one or more adhesives that may be disposed on or in the functional layer. And the optical fiber article may at least partially have a reaction product of a functional silane and a reactive adhesive component. Preferably, the entire optical fiber article is not glued with an adhesive, but only a partial area of the article has a reaction product of a functional silane and at least one adhesive. In one embodiment, the optical fiber article has one or more adhesives on or in the functional layer only over a length of at most 25 mm, in particular at most 15 mm or at most 10 mm. If too large a section of the optical fiber article is glued, the risk of fiber breakage increases. In one embodiment, the optical fiber article has one or more adhesives on or in the functional layer over a length of at least 1 mm, in particular at least 3 mm.
[0126] Adhesives that can be used according to the invention, capable of bonding optical fibers to each other or to other materials, are for example epoxy resin adhesives, acrylate adhesives, cyan adhesives, polyurethane adhesives, silicone adhesives, phenolic resin adhesives, polysulfide adhesives and / or bismaleimide adhesives. In an embodiment, the fiber article has less than 10% by weight of adhesive, more preferably less than 8% by weight, more preferably less than 6% by weight, more preferably less than 4% by weight, more preferably less than 2% by weight, more preferably less than 1% by weight, more preferably less than 0.8% by weight, more preferably less than 0.6% by weight, more preferably less than 0.4% by weight, more preferably less than 0.1% by weight.
[0127] Preferably, the optical fiber article has a functional layer on the optical fiber of at most 10% by weight, more preferably at most 8% by weight, more preferably at most 6% by weight, more preferably at most 4% by weight, more preferably at most 2% by weight, more preferably at most 1% by weight, more preferably at most 0.5% by weight, more preferably at most 0.2% by weight, more preferably at most 0.1% by weight. Preferably, the optical fiber article has a protective layer on the optical fiber of at least 0.001% by weight, more preferably at least 0.005% by weight, more preferably at least 0.009% by weight, more preferably at least 0.012% by weight, more preferably at least 0.02% by weight, more preferably at least 1% by weight, more preferably at least 0.04% by weight, more preferably at least 0.06% by weight, more preferably at least 0.08% by weight. In a preferred embodiment, the optical fiber article has a protective layer on the optical fiber of 0.001 to 10% by weight, more preferably 0.005 to 8% by weight, more preferably 0.009 to 6% by weight. If the proportion of the protective layer is too low, the optical fiber will suffer from poor mechanical, chemical and thermal stability, whereas if the proportion of the protective layer is too high, the integrity of the optical fibers will be reduced, for example in an optical fiber bundle.
[0128] Preferably, the functional layer has a thickness of at least 0.1 nm, more preferably at least 0.9 nm, more preferably at least 1.2 nm, more preferably at least 1.5 nm, more preferably at least 1.8 nm, more preferably at least 2.1 nm, more preferably at least 3 nm. Preferably, the functional layer has a thickness of at most 500 nm, more preferably at most 200 nm, more preferably at most 100 nm, more preferably at most 50 nm, more preferably at most 20 nm. If the functional layer is too thin, the optical fiber will lose mechanical, chemical and thermal stability. If the functional layer is too thick, the optical fiber will lose its cohesion, for example in an optical fiber bundle.
[0129] The optical fiber preferably includes at least one functional layer. In embodiments, the optical fiber includes at least two functional layers, at least three functional layers, or at least four functional layers. Multiple functional layers improve the bending strength of the optical fiber and improve protection against microcracks.
[0130] Preferably, the method for producing an optical fiber article comprises the following steps: a. providing at least one optical fiber; b. coating at least a portion of the optical fiber with a focusing agent; c. Drying the sizing agent Includes.
[0131] For example, the optical fiber can be prepared by drawing methods known to those skilled in the art, for example from a preform, or by nozzle methods.
[0132] Coating of the optical fiber can be performed according to methods known to those skilled in the art, for example, in a dip bath, by spraying the fiber, or by roll-to-roll techniques.
[0133] The functional layer is formed by the dried sizing agent. The drying of the sizing agent affects the properties of the functional layer. The functional layer is preferably dried by a gas mixture. In a preferred embodiment, the gas mixture is air.
[0134] The air humidity of the gas mixture influences the drying and material properties of the functional layer. The term air humidity refers to the relative air humidity. Preferably, the gas mixture has an air humidity of at least 10%, more preferably at least 15%, more preferably at least 20%, more preferably at least 25%, more preferably at least 30%, more preferably at least 35%. Preferably, the gas mixture has an air humidity of at most 95%, more preferably at most 85%, more preferably at most 75%, more preferably at most 60%, even more preferably at most 55%. In a preferred embodiment, the gas mixture has an air humidity of 10% to 95%, 15% to 85% or 20% to 60%. If the air humidity of the gas mixture is too low, in particular the functional silane and / or any alkyl silane and / or any PEG silane will be less likely to react with the surface of the fiber. The functional layer will therefore be less likely to adhere to the fiber. If the air humidity of the gas mixture is too high, the bundling agent dries too slowly, impairing the mechanical and chemical durability of the optical fiber, and if the air humidity is too high, the functional layer will retain too much water and / or water-miscible solvents.
[0135] Temperature influences the drying and material properties of the functional layer. Temperature refers to the temperature of the gas mixture surrounding the fiber during drying and / or the temperature of possible contact surfaces with which the fiber may come into contact during drying, such as heated or unheated spools and / or other fibers. Preferably, the fiber is exposed to a temperature of up to 120°C during drying, more preferably up to 100°C, more preferably up to 80°C, more preferably up to 50°C, more preferably up to 40°C, even more preferably up to 30°C. Preferably, the fiber is exposed to a temperature of at least 8°C, more preferably at least 15°C, more preferably at least 18°C, more preferably at least 20°C, more preferably at least 21°C, even more preferably at least 22°C during drying. In a preferred embodiment, the fiber is exposed to a temperature of 8-120°C, more preferably 15-100°C, more preferably 18-30°C during drying. If the temperature of the gas mixture during drying is too high, undesirable chemical side reactions and undesirable by-products occur. Moreover, if the temperature of the gas mixture during drying is too high, the adhesion of the functional layer to the surface of the fiber will be poor, and if the temperature of the gas mixture during drying is too low, the drying of the bundling agent will be too slow, which will impair the mechanical and chemical durability of the optical fiber and will leave too much water and / or aqueous solvent residue in the functional layer.
[0136] Often the focusing agent is exposed to UV radiation for curing, however, it is preferred that the fiber optic article is not subjected to any curing process and is not dried by UV radiation.
[0137] In one embodiment, the method comprises treating a dry sizing agent (dry sizing agent) with a liquid component to obtain a wet sizing agent as the functional layer, the liquid component having a boiling point of more than 100°C or more than 200°C at 1013 hPa. The liquid component may be selected from the group consisting of silicone oils, polyethylene glycols, alcohols (e.g. long chain or polyhydric), esters, ethers, ketones, acetates and combinations thereof. The dry sizing agent generally comprises less than 50% by weight, in particular less than 35% by weight, of the liquid component. The wet sizing agent preferably comprises at least 35% by weight, in particular up to 85% by weight, of the liquid component. In one embodiment, the proportion of the liquid component in the wet sizing agent is 35-65% by weight.
[0138] According to the invention, optical fiber articles having such a wet sizing agent as a functional layer can also be produced, in particular by the method described herein. The optical fiber article having the wet sizing agent can have the characteristics described as advantageous herein, with the proviso that the functional layer has a proportion of at least 35% by weight of the liquid component described for the wet sizing agent.
[0139] In the processing of glass fiber bundles, a distinction is made between so-called dry and wet sizing agents as functional layers. In the case of wet sizing agents, the individual fibers are glued together in a bundle. It can thus be achieved that the individual fibers fan out less and that they are also less electrostatically charged. It can thus be achieved, for example, that the threading of the fiber bundles into sleeves can be significantly facilitated, which helps to reduce assembly operations. In particular, an increase in the fiber packing density can thus also be achieved, which improves the transmission of the light bundle. Furthermore, the assembly process is likewise simplified, especially in the case of relatively long light guides.
[0140] In contrast, when using a dry sizing agent, the individual fibers are less likely to adhere together. This is advantageous, for example, when the individual fibers need to be further mixed individually and / or in the bundle to achieve a more uniform illumination (also called "randomization process"), or when in a multi-arm bundle the fibers of the individual arms need to be attached as uniformly as possible, i.e. statistically well distributed, to a common final sleeve. In this case, a wet sizing agent would therefore be rather a hindrance.
[0141] Advantageously, the approach of the invention allows a dry sizing agent to be applied as a functional layer on the fiber article first. Only by adding a liquid component, which is a liquid with a high boiling point, preferably above 100° C., more preferably above 200° C., can a customer-specific or application-specific wet sizing agent be provided from the dry sizing agent, which is a clear advantage in the manufacturing process. In principle, it is conceivable to apply the dry sizing agent to the fiber article first and, if necessary, add the liquid component in a subsequent coating process. Thus, the properties of the sizing agent can be targeted according to the customer's wishes or the application. Here, the liquid component can consist of at least one of the following components: silicone oils, polyethylene glycols, alcohols (e.g. long-chain or polyhydric), esters, ethers, ketones, acetates and combinations thereof are suitable as components of the liquid component. The concentration of the liquid component in the functional layer on the fiber article is generally less than 50% by weight, preferably less than 35% by weight, of the dry sizing agent. In the case of wet sizing agents, this proportion is at least 35% by weight and generally ranges from 35 to 65% by weight.
[0142] The fiber optic articles in the fiber bundle are preferably used as light guides and / or image guides, For example, the fiber optic articles can be used in endoscopes, inspection cameras, microscopes and / or spectroscopies.
[0143] The fiber optic article is preferably used in diagnostic or therapeutic procedures, for example, the fiber optic article may be used in endoscopy and / or surgery using flexible inspection cameras. [Brief description of the drawings]
[0144] [Figure 1] Schematic diagram of an optical glass fiber having a fiber core (1) and a cladding (2). A functional layer (3) is bonded to the surface of the cladding layer via covalent siloxane bonds (4) and non-covalent hydrogen bridge bonds (5). The functional layer may include, for example, alkylsilanes (6), aminosilanes (7), polyethylene glycols (8), and fatty acids (9). [Diagram 2] FTIR-ATR spectrum of Example E14. [Diagram 3] FTIR-ATR spectrum of Example E18. [Figure 4] 1 shows the FTIR-ATR spectra of commercially available fiber articles. [Diagram 5] 1 shows the FTIR-ATR spectra of commercially available fiber articles. [Figure 6] 1 shows the FTIR-ATR spectra of commercially available fiber articles. [Figure 7] The bending radius achieved in the broken loop test as a function of the duration of use of the sizing solution is shown in comparison with a sizing solution from the prior art (individual values). [Figure 8] 1 shows the change in bend radius of a fiber according to the invention in a breaking loop test after frequent temperature changes. [Figure 9] 1 shows the change in light transmission of a fiber bundle according to the present invention after hundreds of cleaning and sterilization cycles. [Figure 10] 4 shows the change in irradiation intensity achieved after repeated bending with a fiber with a coating according to the invention compared to the prior art without functional silane.
[0145] Working Example Example E1 To prepare the focusing solution, the following components (each from Sigma Aldrich) were weighed into a solution of ethanol, deionized water, and acetic acid in a 1 L laboratory vial and stirred on a laboratory standard magnetic stir plate for at least 1 hour:
[0146] [Table 24]
[0147] Example E2~E22 To prepare the bundling agent solution, the components listed in Tables 1, 2 and 3 (each from Sigma Aldrich) were weighed into a solution of ethanol, deionized water, optionally acetic acid, and optionally further solvents such as dipropylene glycol monomethyl ether or tripropylene glycol monomethyl ether in a 1 L laboratory glass bottle and stirred for at least 1 hour on a laboratory standard magnetic stir plate. Table 1 shows the components of Examples E2 to E18 in relative weight % without solvents such as ethanol, deionized water or acetic acid. PEG-Si=2-[methoxy(polyethyleneoxy)9-12propyl]trimethoxysilane, Ami-Si=N-[3-(trimethoxysilyl)propyl]ethylenediamine, Alk-Si=trimethoxy(octyl)silane. The bundling agent solution was then applied to the optical fiber by roll-to-roll technique and dried at room temperature. Table 1 also provides information on the extrusion force and whether the fiber-sleeve (FH) bond or the fiber-fiber (FF) bond broke during the extrusion test. Additionally, the break length is given.
[0148] [Table 25]
[0149] [Table 26]
[0150] [Table 27]
[0151] The IR spectrum was measured from the optical fiber glass fiber bundle coated with the focusing agent solution. The measurement was carried out for one glass fiber bundle. For this purpose, the glass fiber bundle was pressed against the ATR crystal of the measuring device several times. Here, a small amount of the focusing agent was transferred to the crystal and measured. The FTIR-ATR spectrum of sample E14 is shown in Figure 2, and the FTIR-ATR spectrum of sample E18 is shown in Figure 3.
[0152] Example E23 and E24 As described in Examples E2-E22, sizing solutions were prepared using water and ethanol, but without acetic acid.
[0153] [Table 28]
[0154] The extrusion force was very good for both sizing solutions, with E24 achieving superior values only at the elevated temperature.
[0155] It was investigated how the bending radius of a fiber coated with sizing agent E23 changes depending on the duration of use of the sizing solution. The results are shown in Figure 7. It can be seen that the bending radius is initially just above 1 mm and increases somewhat depending on the duration of use of the sizing solution up to a range of around 1.6 mm. Only after 288 hours is a bending radius comparable to that of the prior art without functional silane (separate measurement points) reached.
[0156] Figure 8 shows how the results of the breaking loop test change after exposing the fibres to frequent temperature changes. Here, the bundles were cooled or heated 50 times from -40°C to +80°C at a rate of 2K / min at 0% air humidity. It was found that the fibres treated with E23 and E24 showed the same very good results in the breaking loop test after the test as before the test. The comparative fibres coated with a sizing agent according to the prior art (without functional silane) showed significant degradation. Storage at 85°C and 85% air humidity for 400 hours gave equally good results as storage in hot water at 90°C for 10 days.
[0157] Fiber bundles coated with a bundling agent solution were used to determine how their transmission deteriorated under heavy cleaning loads. For this purpose, the fiber bundles were subjected to 500 cycles of cleaning and subsequent thermal disinfection, with 20 cleaning steps followed by 50 sterilization steps each. Figure 9 shows that the transmission of the fibers treated with the bundling agent according to the invention (squares = E23; triangles = E24) deteriorated slightly to about 97%, while the comparative bundles (circles; without functional silane) partially dropped to 90%. These data indicate good chemical resistance and hydrolytic stability.
[0158] Figure 10 shows the evolution of the irradiation intensity obtained after repeated bending to a bending radius of 2 mm, with bending angles from -90° to +90°, a cycle time of 2 seconds, and an axial load of 5 N, according to IEC 60794-1-6 / E6. It can be seen that the bundling solution E23 (squares) gives the best results; E24 (triangles) is better than the prior art without functional silanes (diamonds). [Explanation of symbols]
[0159] 1 Fiber Core 2. Clad 3. Functional Layer 4. Siloxane bonding between the alkylsilane of the functional layer and the surface of the cladding layer 5 Hydrogen cross-linking between the functional groups on the surface of the cladding layer and the polyethylene glycol of the functional layer 6. Alkylsilanes 7. Aminosilane 8. Polyethylene Glycol 9 fatty acids
Claims
1. 1. An optical fiber article comprising at least one optical fiber and a functional layer disposed on a surface of the optical fiber, wherein the functional layer has the following structural formula: 【Chemistry 1】 wherein Z is a branched or unbranched alkyl or aryl group having 1 to 18 carbon atoms; R1, R2 and R3 are independently selected from hydrogen, oxygen, alkyl, alkyloxy, hydroxyalkyl and hydroxyl, and one, two or three of the groups R1, R2 or R3 are directly or indirectly attached to the surface of said optical fiber via a covalent bond; and R4 is -NH 2 , —NHR′, —NR′R″, glycidyloxy, and —SH, where R′ and R″ are selected from alkyl, aminoalkyl, hydroxyalkyl, and —(CH 2 ) m N.H. 2 and m is 1 to 6.
1. A fiber optic article comprising at least one functional silane having the formula:
2. 2. The optical fiber article of claim 1, wherein the content of photopolymerized polymers in the functional layer, in particular polyacrylates, polymethacrylates, polyvinyl polymers, polystyrene and / or their derivatives, is less than 1% by weight, based on the mass of the functional layer.
3. 3. The optical fiber article of claim 1 or 2, containing less than 500 ppm (m / m) of halides.
4. The optical fiber article of claim 1 , wherein the functional layer further comprises at least one fatty acid.
5. The optical fiber article of any one of claims 1 to 4, wherein the at least one optical fiber has a bend radius of less than 10 mm in the breaking loop test according to DIN 58141-6:2011.
6. The optical fiber article of any one of claims 1 to 5, having a push-out force of at least 250N.
7. 7. The optical fiber article of any one of claims 1 to 6, which is biocompatible according to ISO 10993-1:2018, USP Class VI and / or ISO 10993-5:2009.
8. The optical fiber article of claim 1 , wherein the functional layer comprises an alkyl silane and / or a polyethylene glycol silane covalently bonded to a surface of the fiber.
9. R4 is -NHR', where R' is -(CH 2 ) m N.H. 2 9. The optical fiber article of any one of claims 1 to 8, wherein m=2 and Z is an unbranched alkyl group having 1 to 10 carbon atoms, preferably 3 to 8 carbon atoms.
10. The optical fiber article according to any one of claims 1 to 9, wherein the functional layer comprises a polyalkylene oxide, in particular a polyglycol.
11. The optical fiber article of claim 1 , wherein the optical fiber has a fiber core and a cladding, and the functional layer is disposed on a surface of the cladding.
12. The optical fiber article of any one of claims 1 to 11 having a fiber core and / or cladding made from a multicomponent glass.
13. 1. An optical fiber article comprising at least one optical fiber and a functional layer disposed on a surface of the optical fiber, the functional layer having the following absorption in the IR spectrum: a. 1500 cm -1 ~1900cm -1 for maximum absorption band height in the range of 800 cm -1 ~1200cm -1 the ratio of maximum absorption band heights in the range of at least 2.0; b. 1500 cm -1 ~1900cm -1 for the maximum absorption band height in the range of 2700 cm -1 ~3000cm -1 the ratio of maximum absorption band heights in the range of at least 2.0; and c. 2700 cm -1 ~3000cm -1 for maximum absorption band height in the range of 800 cm -1 ~1200cm -1 The ratio of the maximum absorption band heights in the range of at least 1.1 and at most 2.0 A fiber optic article comprising:
14. 14. The optical fiber article of claim 13 having an IR spectrum substantially in accordance with FIG. 2 or FIG.
3.
15. 15. The optical fiber article according to claim 1, having a dry functional layer in which the proportion of liquid components with a boiling point above 100° C. at 1013 hPa is less than 35% by weight.
16. 15. The optical fiber article according to any one of claims 1 to 14, having a wetted functional layer with a proportion of liquid components with a boiling point above 100°C at 1013 hPa of at least 35% by weight.
17. 17. The optical fiber article of any one of claims 1 through 16, wherein the functional silane at least partially forms a reaction product with one or more adhesives.
18. Steps below: a. providing at least one optical fiber; b. coating at least a portion of the optical fiber with a bundling agent; c) drying the sizing agent A method for producing the optical fiber article of any one of claims 1 to 17, comprising:
19. 20. The method of claim 18, comprising treating the dry sizing agent with a liquid component to obtain a wet sizing agent, the liquid component having a boiling point greater than 100°C at 1013 hPa.
20. 20. The method of claim 19, wherein the liquid component is selected from the group consisting of silicone oils, polyethylene glycols, alcohols, esters, ethers, ketones, acetates, and combinations thereof.
21. 17. Use of the fiber optic article according to any one of claims 1 to 16 in a fiber bundle as a light guide and / or image guide, for example in an endoscope.
22. 17. The fiber optic article of any one of claims 1 to 16 for use in diagnostic or therapeutic methods.
Citation Information
Patent Citations
Production of optical fiber
JP1988011550A
Optical waveguide module
JP2006184757A
Optical transmission body
JP2017007875A